Theft, patronage & society in Western India - Piliavsky, A; Anastasia Piliavsky (2011)
This thesis is an ethnography of a community of professional thieves called the Kanjar-a 'caste of thieves' by practice, public perception and self-designation-in the northern Indian province of Rajasthan. It is also an argument that spells out the broader logic of rank in local society. Insofar as it offers the first ethnography of the Kanjar community- and of caste-based, professional, hereditary theft-this study is new. My analytical concern with hierarchy and rank, however, is old, engaging in the once central, and now largely out-fashioned, discussion in the sociology of South Asia. My project began with a narrow set of concerns with the place of thieving and thieves in local society. In the course of my fieldwork, however, it became apparent that the received wisdom of South Asian sociology regarding the principles of rank did not offer useful explanatory tools and that a different conception of rank was necessary to make sense of what I observed, both about the social position of Kanjars and the hierarchical social formation at large. As is so often the case, what began as a study of historically and sociologically particular circumstances became an inquiry into the pervasive regnant aspects of the local order of things.